2002
DOI: 10.1007/s00417-002-0518-3
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological correlation of corneal diseases with optical coherence tomography

Abstract: Noncontact slitlamp-adapted corneal OCT revealed a good correlation with histological sections. The differences noted were partly related to shrinking processes during preparation. Thus, with certain limitations, OCT allows a non-invasive optical biopsy of pathological structures in corneal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…However, slight postoperative thickness changes in the flap and residual stroma were possibly related to different hydration levels in the anterior and posterior stroma. 6,10 In conclusion, this case confirmed that ocular surgery may diminish the endothelial pump function and produce clinically significant edema and interface fluid in corneas treated with LASIK. 4,5 Although the IOP as measured by applanation tonometry did not increase in the presence of interface fluid, 1-3 marked edema in the residual stromal bed could have been aggravated by an increased IOP after RD surgery.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, slight postoperative thickness changes in the flap and residual stroma were possibly related to different hydration levels in the anterior and posterior stroma. 6,10 In conclusion, this case confirmed that ocular surgery may diminish the endothelial pump function and produce clinically significant edema and interface fluid in corneas treated with LASIK. 4,5 Although the IOP as measured by applanation tonometry did not increase in the presence of interface fluid, 1-3 marked edema in the residual stromal bed could have been aggravated by an increased IOP after RD surgery.…”
Section: Discussionsupporting
confidence: 80%
“…Corneal OCT also imaged the significant fluid collection in the interface as a space with low reflectivity. 10,11 This layer of fluid had a depth of more than 100 mm, which was significantly more than previously reported. 1 In this case, the main pathophysiologic mechanism was presumably a transient corneal endothelial cell dysfunction after vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 72%
“…14,25,26 Optical coherence tomography is thought to achieve a higher resolution (ie, a few micron) than computer tomography or magnetic resonance imaging 27 ; therefore, this noninvasive technique is also referred to as optical biopsy. 28,29 Pentacam imaging is based on the Scheimpflug principle (Theodor Scheimpflug, 1904, 30 and Jules Carpentier, 1901 31 ); that is, when the lens is tilted relative to the film plane, the lens plane, film plane, and the plane of focus are not parallel to one another and then the 3 major planes intersect in a common straight line. Because of this configuration, anterior segment structures (lying in the same plane of focus) from the front corneal surface to the back surface of the lens can be sharply focused ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The sample arm of the interferometer and the scanning module were integrated in the projected slit of a standard clinical slit lamp (SL-3C, Topcon, Tokyo, Japan) as described previously. [4][5][6][7][8][9] For the tomographic representation, the reflected light was analyzed, and the intensity was converted to logarithmic gray-scaled images, which were simultaneously recorded during the measurements. Slit-lampadapted OCT enabled determination of the thickness using the axial interference profile of the reflections.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7][8][9] In previous clinical evaluations, we demonstrated that slit-lamp-adapted OCT enabled cross-sectional and high-resolution imaging of the cornea [4][5][6][7][8][9] and that there was a positive correlation of the optical corneal changes with histologic findings. 8,9 In this study, imaging of calcified corneal lesions with OCT was performed to evaluate its potential to assess external corneal diseases.…”
mentioning
confidence: 96%